2015
DOI: 10.1002/mabi.201500186
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric AB3 Miktoarm Star Polymers: Synthesis, Self‐Assembly, and Study of Micelle Stability Using AF4 for Efficient Drug Delivery

Abstract: A simple and versatile methodology, which employs a combination of ring-opening polymerization and alkyne-azide click chemistry to synthesize amphiphilic AB3 miktoarm stars, is reported. Their aqueous self-assembly behavior was studied using dynamic light scattering, fluorescence, and asymmetrical flow field-flow fractionation (AF4). AB3 miktoarm stars form micelles which incorporate curcumin with high efficiency, and significantly reduce the viability of glioblastoma cells in spheroids. We demonstrate that AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Polymeric carriers have the potential to improve the stability and solubility of curcumin [60][61][62]. Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64]. A retention of curcumin's biological activity in nanocarriers, an enhanced permeability and retention (EPR) effect and diffusion of curcumin into the neighboring glioblastoma cells could provide an improved therapeutic intervention in vivo [65] Pyrrolidine-2 is an inhibitor of cPLA2a, a key rate limiting enzyme in the synthesis of eicosanoids and a necessary player in the formation of lipid droplets [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric carriers have the potential to improve the stability and solubility of curcumin [60][61][62]. Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64]. A retention of curcumin's biological activity in nanocarriers, an enhanced permeability and retention (EPR) effect and diffusion of curcumin into the neighboring glioblastoma cells could provide an improved therapeutic intervention in vivo [65] Pyrrolidine-2 is an inhibitor of cPLA2a, a key rate limiting enzyme in the synthesis of eicosanoids and a necessary player in the formation of lipid droplets [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an AB 2 polymer where B segments are added by click chemistry, the relative integrations of B-derived protons become double, compared to those from the A segment. Analysis of its GPC chromatogram showed a unimodal peak, implying that there are no unconjugated segments [ 24 , 38 , 46 , 53 , 55 ].…”
Section: Synthetic Approaches To Miktoarm Star Polymersmentioning
confidence: 99%
“…Micellar drug retention has generally been associated with more sustained drug release and dampening burst release [ 32 , 48 , 55 , 70 ], which has the benefit of increasing drug bioavailability. This could be the result of strong interactions and more sites of association between the encapsulated drug and multiple hydrophobic chains [ 27 , 52 , 70 , 133 ].…”
Section: Amphiphilic Miktoarm Star Polymers: Self-assemblymentioning
confidence: 99%
“…This suggests that the telodendrimer assumes a hydrophobic core/hydrophilic corona type structure in D2O. We examined similar self-assembly of the telodendrimer using an acetone/water co-solvent evaporation method [34][35][36]. The resulting assemblies were characterized using dynamic light scattering (DLS) and transmission electron microscopy (TEM) ( Figure 3).…”
Section: Synthesismentioning
confidence: 99%